2006
DOI: 10.1158/0008-5472.can-05-2445
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Stem Cell Genes, Including Those in a 200-kb Gene Cluster at 12p13.31, Is Associated with In vivo Differentiation of Human Male Germ Cell Tumors

Abstract: Adult male germ cell tumors (GCTs) comprise distinct groups: seminomas and nonseminomas, which include pluripotent embryonal carcinomas as well as other histologic subtypes exhibiting various stages of differentiation. Almost all GCTs show 12p gain, but the target genes have not been clearly defined. To identify 12p target genes, we examined Affymetrix (Santa Clara, CA) U133A+B microarray (f83% coverage of 12p genes) expression profiles of 17 seminomas, 84 nonseminoma GCTs, and 5 normal testis samples. Seventy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
258
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(287 citation statements)
references
References 43 publications
20
258
0
9
Order By: Relevance
“…A total of 32 specimens were primary testicular tumors, 8 were from patients with mediastinal primaries or metastases, and the remaining 34 were from metastatic sites other than the mediastinum. All of these samples were previously profiled for expression using Affymetrix U133A1B microarrays [GEO Accession Number GSE3218; see (Korkola et al, 2006) for further information].…”
Section: Tumor Specimensmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 32 specimens were primary testicular tumors, 8 were from patients with mediastinal primaries or metastases, and the remaining 34 were from metastatic sites other than the mediastinum. All of these samples were previously profiled for expression using Affymetrix U133A1B microarrays [GEO Accession Number GSE3218; see (Korkola et al, 2006) for further information].…”
Section: Tumor Specimensmentioning
confidence: 99%
“…All of the tumors that were used for this study were previously profiled using Affymetrix U133A1B microarrays for expression analysis (Korkola, et al 2005(Korkola, et al , 2006, facilitating the identification of potential target genes that mapped to altered regions. We focused on regions that had at least two contiguous BAC clones that were altered in at least 40% of cases, and looked for genes that were significantly differentially expressed with at least a twofold change relative to tumors without the alteration or fourfold relative to normal testes.…”
Section: Target Gene Identification In Frequently Altered Regionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with our previous report (Rogulski et al, 2005b), a notable correlation between c-Myc and GpIba expression was seen (Figure 6b). Finally, a search of the Oncomine database (http://www.oncomine.org; Rhodes et al, 2004) indicated that GpIba transcripts were overexpressed in germ cell tumors vs normal testicular tissue (P ¼ 0.001; Korkola et al, 2006), in imatinibresistant chronic myelogenous leukemia vs untreated chronic-phase disease (P ¼ 7 Â 10 À7 ; Radich et al, 2006;Figure 6c), and in c-src-transformed primary human mammary epithelial cells (Bild et al, 2006).…”
Section: Increased Expression Of Gpiba In Cancermentioning
confidence: 99%